Pedagogical Education in the Context of Non-Formal Education: Historical Aspect - Bondar, Tetiana (Educational Challenges, 2020)
The purpose of the article is to study the organization of pedagogical education of adults by the Society ‘Knowledge’ in Ukraine in the second half of the XX-early XXI century in the context of non-formal education. The research methodology was conducted on the basis of general scientific, historical-pedagogical, terminological and prognostic methods. The results are the experience of pedagogical education of adults both positive and negative in the context of non-formal education. The tendencies, as well as directions and forms of the organization of pedagogical education of adults on an example of Society ‘Knowledge’ are revealed and presented. It was found out that the leading directions of pedagogical education of this Society in the studied period were lecture activities organized in different forms. In particular, ‘Lectures and schools for parents’, which raised the issues of upbringing children of preschool and school age. There were people’s pedagogical universities for additional education of teachers on children’s upbringing. A network of ‘Young Mother Schools’ was opened, which also raised issues of education and development of preschool children. ‘Women’s clubs’ were also organized, where scientific and educational pedagogical activity among women was carried out. A network of research and educational centers was launched, the activities of which were aimed at providing educational services, retraining, obtaining additional professions, courses, seminars, excursions, exhibitions, distance learning courses and webinars, etc. Distance learning software was developed and used for the Adult Distance Learning System, particularly in the field of education. The conclusions are the organization of pedagogical education of adults by the Society ‘Knowledge’ during the second half of XX – early XXI century is divided into two periods: the Soviet (1949 – 1990) and the period of independent Ukraine (1991 – 2018). The experience can be taken into account when reforming education in different countries, in particular non-formal education.